Kode Etik Profesi Akuntan Publik Ditinjau dari Perspektif Islam - Febi Annuri Jayasi (IAIN Madura, 2022)
This study aims to analyze the Code of Ethics of the Public Accountant Profession from an Islamic Perspective. This research is a qualitative research with library research. This type of library research uses the texts of the Qur'an and Hadith or more often called the study of revelational texts. For the method of analysis using the Content Analysis Method. Understanding the five principles of professional ethics for Public Accountants From an Islamic perspective based on the Qur'an and hadith, a Public Accountant with integrity built from spiritual and emotional intelligence is objective in making decisions or judgments about a matter by being fair and careful with full consideration , encourage to be careful about work, have a trustworthy nature and maintain the confidentiality of information. Therefore, Islamic teachings provide instructions for public accountants to always understand and obey orders and stay away from Allah's prohibitions.